The influence of sucking habits on occlusion development in the first 36 months A influência dos hábitos de sucção no desenvolvimento oclusal nos primeiros 36 meses - Edson Theodoro dos Santos Neto; Adauto Emmerich Oliveira; Rodrigo Walter Barbosa; Eliana Zandonade; Zilda Fagundes Lima Oliveira (Dental Press Editora, 2012)
OBJECTIVE: The objective of this study was to identify the influence of sucking habits on the occlusal characteristics of the deciduous dentition. METHODS: The initial sample consisted of 86 infants, aged 0 to 3 months. Seven home visits were performed, when and information on breastfeeding practice, nutritive and non-nutritive sucking habits, mouth breathing and dentition development was collected. From the first sample, impressions of the dental arches were obtained from 58 children at the age of 36 months (+2.51SD). Dental casts were obtained and two examiners, trained and calibrated by the Kappa and Pearson Correlation tests, measured several parameters of dental occlusion, such as arch length, depth, and width. RESULTS: The results showed that bottle feeding before 6 months was associated to an increased mandibular intermolar width (p=0.01). Pacifier use before 6 months was statistically associated to a reduction of the maxillary intercanine (p=0.03) and intermolar (p=0.03) width. In addition to these findings, the increased molar depth of the maxillary arch was associated to loss of lip closure before the age of 12 months (p= 0.03). CONCLUSION: According to these results, it could be concluded that sucking habits interfere with the determination of some deciduous occlusal characteristics: pacifier sucking limits lateral-lateral maxillary growth, bottle feeding favors lateral-lateral mandibular growth and open bite development, and the lack of lip closure favors the anteroposterior maxillary growth. OBJETIVO: a proposição do estudo foi verificar a influência dos hábitos de sucção nas características oclusais da dentição decídua. MÉTODOS: o grupo inicial constituiu-se de 86 bebês com idade de 0 a 3 meses. Sete visitas domiciliares foram realizadas, quando informações sobre a prática da amamentação, hábitos de sucção nutritivos e não-nutritivos, respiração bucal e desenvolvimento da dentição foram coletados. A partir do grupo inicial, 58 crianças foram moldadas em consultório na idade média de 36±2,51 meses. Modelos de estudo foram obtidos e medidos diversos parâmetros da oclusão dentária, tais como profundidade, extensão e largura das arcadas, por dois examinadores comprovadamente calibrados pelo teste de concordância Kappa e correlação de Pearson. RESULTADOS: os resultados demonstraram que o aleitamento artificial por mamadeira antes dos 6 meses esteve associado à largura intermolares inferior (p=0,01). A sucção de chupeta antes dos 6 meses foi estatisticamente associadaà diminuição da largura intercaninos superior (p=0,03) e intermolares superior (p=0,03). Somando-se a isso, o aumento da extensão molar da arcada superior associou-se à perda do vedamento labial antes dos 12 meses de vida (p=0,03). CONCLUSÃO: é possível concluir-se que os hábitos de sucção interferem na determinação de características oclusais na dentição decídua. A sucção de chupeta limita o crescimento da arcada superior; o uso de mamadeira favorece o crescimento laterolateral da mandíbula e o desenvolvimento da mordida aberta; e a ausência de vedamento labial favorece o crescimento maxilar anteroposterior.